Strategic Management of Dormitory Facilities in Islamic Educational Institutions: Enhancing Student Discipline and Academic Achievement - Taufiq, Muhammad (Program Pascasarjana Institut Agama Islam Darullughah Wadda'wah Bangil Pasuruan, 2025)
Dormitory facilities in Islamic educational institutions play a pivotal role in fostering discipline and supporting academic achievement among students. However, many institutions face challenges in maintaining effective management due to limited resources and inconsistent policies. This study aims to explore the strategic management of dormitory facilities and its impact on student discipline and academic achievement. Employing a qualitative case study approach, data were collected through semi-structured interviews, observations, and document analysis at Dalwa 4 dormitory, Pondok Pesantren Darullughah Wadda’wah. The findings reveal that strategic planning, resource optimization, leadership practices, and student engagement programs are key factors in achieving effective dormitory management. Structured routines and transformational leadership approaches significantly enhance discipline, while well-maintained facilities and engagement activities contribute to improved academic outcomes. Additionally, mnemonic techniques were found to reduce student anxiety and support learning retention. This study contributes to the literature by providing a comprehensive framework that integrates strategic planning, leadership, and engagement practices for holistic student development. It offers practical recommendations for administrators to optimize dormitory management and suggests future research to include multi-institutional and mixed-method approaches for broader generalization.